2018
DOI: 10.1615/jenvironpatholtoxicoloncol.2018025226
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Apoptotic Effect of Juglone on Human Bladder Cancer TCC-SUP and RT-4 Cells: An In Vitro Study

Abstract: This study aimed to investigate the effects of juglone on the human bladder carcinoma cell lines TCC-SUB and RT-4 in monolayer and spheroid cultures. Cells were treated with juglone at 24, 48, and 72 h of incubation. The activity of caspase-3 was detected in vitro using a caspase-3 colorimetric assay kit according to the manufacturer's instructions. The bromodeoxyuridine (BrdU) labeling index was used to determine the cells of the synthesis phase. The terminal deoxynucleotidyl transferase-mediated dUTP nick en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The cytotoxic effect of juglone on human breast cancer cell line MCF-7 is characterized by elevated ROS levels, reduced Bcl-2 expression, increased Bax expression, decreased mitochondrial membrane potential, increased intracellular Ca 2+ concentration, outer mitochondrial-membrane rupture, cytochrome c release, and caspase-3 activation [91]. According to a recent study, juglone significantly inhibits the proliferation and induces the apoptosis of human bladder carcinoma cell lines (TCC-SUB and RT-4) [92].…”
Section: Anticancer Effects Of Juglonementioning
confidence: 99%
“…The cytotoxic effect of juglone on human breast cancer cell line MCF-7 is characterized by elevated ROS levels, reduced Bcl-2 expression, increased Bax expression, decreased mitochondrial membrane potential, increased intracellular Ca 2+ concentration, outer mitochondrial-membrane rupture, cytochrome c release, and caspase-3 activation [91]. According to a recent study, juglone significantly inhibits the proliferation and induces the apoptosis of human bladder carcinoma cell lines (TCC-SUB and RT-4) [92].…”
Section: Anticancer Effects Of Juglonementioning
confidence: 99%
“…The extracts have also been used in folk medicine for many years for treating cancer. The research conducted thus far has demonstrated the anticancer properties of juglone (Ji et al, 2011 ; Li et al, 2013 ; Fang et al, 2015 ; Delaviz et al, 2017 ; Wu et al, 2017 ; Bayram et al, 2018 ; Bayram et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The antiproliferative properties of juglone have also been confirmed in other studies on various types of cancer cells in vitro . For example, previous studies have demonstrated a strong dose-dependent and time-dependent influence of juglone on the growth of LS-174T colon adenocarcinoma cells (Li et al, 2013 ) and SGC-790 gastric cancer cells (Ji et al, 2011 ) and on the reduction of viability and inhibition of proliferation of SKOV3 ovarian cancer cells through blocking of cell cycle progression (transition from phase G1 to S) (Fang et al, 2015 ); juglone also strongly affected the inhibition of the proliferation of TCC-SUM and RT-4 bladder cancer cells (Bayram et al, 2018 ), MCF-7 breast cancer cells (Ji et al, 2016 ), and CCL-228-SW colon cancer cells (Bayram et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, arbutin markedly elevates p21/ WAF1expression, thereby negatively regulating the cell cycle (114). Juglone is a quinone isolated from the root bark, pericarp, and branch bark of fresh Juglone catalpa and its anticancer activity includes inhibition of proliferation and induction of apoptosis of RT4 and TCCSUP bladder cancer cell lines (115).…”
Section: Quinone Compounds Anthraquinonesmentioning
confidence: 99%